PENGEMBANGAN POTENSI WISATA MANDALA BULEUD DI KAMPUNG PANGKALAN DESA SUKAMULIH KECAMATAN SARIWANGI KABUPATEN TASIKMALAYA - Syadiyah, Siti Halimatus (Universitas Negeri Padang, 2024)
This research discusses the potential of Mandala Buleud Tourism in Kp. Pangkalan, Sariwangi District, Tasikmalaya Regency. The purpose of this research is to find out the problems that exist at tourist locations, and to be able to provide solutions that can be taken into consideration in developing Buleud Mandala tourism and reducing the problems that exist at this tourist attraction. Another objective of this research is so that this tourism can be known more widely by society. This type of research is quantitative descriptive research. The type of data analysis used is primary data analysis, which is obtained directly by researchers in the field from the person concerned. Based on the results of the survey conducted, 4 SWOT analyzes (analysis of strengths, opportunities, weaknesses and threats) were obtained in Mandala Buleud tourism. Some of the advantages of Mandala Buleud tourism include the fulfillment of good tourist attractions. The tourist opportunity for Mandala Buleud is that it is a cool and beautiful natural tourist attraction, and is suitable as a camping spot. The weakness of Mandala Buleud tourism is poor accessibility and lack of tourism promotion to the wider community. The threat faced by Mandala Buleud tourism is the existence of chicken farms and the existence of similar tourist attractions in other areas. Therefore, it can be concluded that the solutions that can be offered based on the results of the field analysis that have been carried out are as follows: developing facilities and infrastructure, developing marketing and branding, establishing collaboration with related parties, and creating sustainable tourism development.